FEKUNDITAS CACING Ascaris suum PADA BABI LANDRACE DI KOTA KUPANG - Dwi R.F.Putri Ully; Aji Winarso; Julianty Almet (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2020)
Pigs have a very important role for the community that is as a source of animal protein, a source of income, savings and jobs. Pigs are susceptible to various diseases, including diseases that are caused by a parasite of Nematodes class, namely Ascaris suum. The purpose of this study was to determine the degree of real infections by parasitic load value, to determine the degree of infection alleged by TTGT value and to determine the fecundity of Ascaris suum in pigs Landrace in Kupang. The sample was 20 adult male Landrace pigs (finisher) were infected with Ascaris suum. The results showed a positive sample of 20 infected worm Ascaris suum by average number of male worm as much as 3 and the average number of female worm as much as 7 as well as the presence of the worm eggs in the stool with the average amount of 4,645 worm eggs as much by using the method of Mc Master. The results of counting the number of eggs per gram of feces (TTGT) showed 19 samples have TTGT number of> 2000 were categorized as heavy infestations, while one sample has a number TTGT <2000 were categorized as moderate infestation.. The results of the calculation of worm Ascaris suum fecundity showed the highest and lowest values of fecundity, that is each 962,666.66 eggs/adult female worm/day and 180.819 eggs/adults female worm/day.. In conclusion, the fecundity of Ascaris suum in Kupang varied.